A data discovery model for incomplete information systems - Africa, Aaron Don M.; Co, Celso B. (2010)
This paper presents a Data Discovery Model to be used in Incomplete Information Systems. A Theorem is proposed about the Information Dependency of Data. Formal proofs of the theorem are presented and verified as to their correctness with some examples.
Keywords: Information management; Database engineering; Rough set theory